Preliminary measurements of carbon and oxygen energy spectra from the second flight of CREAM - ZEI, RICCARDO; H. S. AHN; P. ALLISON; BAGLIESI, MARIA GRAZIA; L. BARBIER; J. J. BEATTY; BIGONGIARI, GABRIELE; T. J. BRANDT; J. T. CHILDERS; N. B. CONKLIN; S. COUTU; M. A. DUVERNOIS; et al. (Universidad Nacional Autónoma de México, 2008)
The Cosmic Ray Energetics and Mass (CREAM) experiment was successfully flown twice on long-duration balloons from McMurdo, Antarctica, in 2004/05 and 2005/06. During the second flight, the redundant charge identification system of the instrument (based on scintillators and silicon detectors) was upgraded with the addition of a second layer of pixelated silicon sensors. A measurement of the particle energy was provided by an ionization calorimeter. From the on-going analysis of the data of the second flight, preliminary results on Carbon and Oxygen spectra up to a few TeV/n will be presented.